Challenges and Solutions in the Construction of the Hong Kong-Zhuhai-Macao Bridge Immersed Tunnel - Li, Yubai (Transactions on Engineering and Technology Research, 2024)
This research aims to systematically analyze the design and construction challenges encountered during the development of the Hong Kong-Zhuhai-Macao Bridge (HZMB) immersed tunnel. By thoroughly examining these challenges, the study seeks to generate valuable insights that can inform future infrastructure projects of similar scale and complexity. A comprehensive understanding of the design principles employed, construction techniques implemented, and risk mitigation strategies utilized throughout the HZMB project will enhance the safety, reliability, and efficiency of immersed tunnel construction. Furthermore, the findings of this research have the potential to stimulate innovation in immersed tunnel technology, leading to the development of more advanced engineering solutions that prioritize sustainability. By addressing the unique complexities associated with immersed tunnels, this research not only contributes to the body of knowledge within civil engineering but also serves as a guide for practitioners and researchers aiming to push the boundaries of infrastructure development. Ultimately, this paper aspires to support the advancement of civil engineering practices, ensuring that future projects are better equipped to meet the demands of modern infrastructure needs.